The solution revolution : how business, government, and social enterprises are teaming up to solve society's toughest problems - Eggers, William D. (Harvard Business Review Press, 2013)
"Welcome to the "Solution Economy" We're at a critical juncture in our global economy, with the siloed ways of the past (public vs. private) quickly fading. Instead, we are witnessing a step change in how society deals with its own problems-in which government acts as just one player among many, and entrepreneurship and innovation range freely across all sectors. Deloitte's William Eggers and Paul Macmillan illustrate this new operating model in the forthcoming book, The Solution Revolution. The authors show that over the past decade, a variety of new and important players have entered the societal problem solving arena, operating within what they call a "Solution Economy." These innovators are closing the widening gap between what governments provide and what citizens need-an approach that promises better results, lower costs, and the best hope we have for public innovation in an era of fiscal constraints and unmet needs. We're still in the early stages of the solution economy's development, but Eggers and Macmillan compellingly lay out the contours of the phenomenon, as well as its primary features, dynamics, and players. They provide advice to business, government, and the social sector on what they can do to strengthen and spread the larger revolution, both locally and globally. The Solution Revolution provides a fascinating preview of our economic future, a system where choice, sustainability, and more adaptive ecosystems offer all of us the ability to collaborate towards better solutions. "--